FISH for All: A Fast and Efficient Fluorescent In situ Hybridization (FISH) Protocol for Marine Embryos and Larvae - Paganos, Periklis; Caccavale, Filomena; La Vecchia, Claudia; D’Aniello, Enrico; D’Aniello, Salvatore; Arnone, Maria Ina (Frontiers in Physiology, 2022)
In situ hybridization is one the most commonly used techniques for developmental and evolutionary biology and has extensively contributed to the identification of distinct cell types and cell states, as well dissecting several molecular mechanisms involved in physiological processes. Moreover, it has been used as a tool to compare distinct gene expression patterns and, therefore, genetic programs across animal species. Nowadays, the predominance of transcriptomics in science has imposed the need to establish a reliable, fast and easy whole mount in situ hybridization protocol. Here we describe a fluorescent in situ hybridization protocol that is rapid, accurate and applicable in a great variety of marine species.